TI_GERICHTE 32.2013.114 vom 14. Mai 2013 , Soppressione della rendita in via di revisione. Perizia reumatologica confermata - TI Tribunale d'appello (2013)
Soppressione della rendita in via di revisione. Perizia reumatologica confermata